Role of vaccination in the sustainability of healthcare systems - Largeron, Nathalie (J Mark Access Health Policy, 2015)
The use of vaccines to prevent diseases in children, adults, and the elderly results in fewer medical visits, diagnostic tests, treatments, and hospitalisations, which leads to substantial savings in healthcare costs each year in Europe and elsewhere. Vaccines also contribute to reducing resource utilisation by preventing nosocomial infections, such as rotavirus gastroenteritis, which can increase hospital stays by 4–12 days. Vaccination also has an important role in the prevention of cancers with, for example, human papillomavirus or hepatitis B vaccines. Since the financial impact of cancer is high for patients, healthcare systems, and society as a whole, any cases prevented will reduce this impact. Newer vaccines, such as the herpes zoster vaccine, can provide an answer to unmet medical needs by preventing and reducing the severity of shingles and associated post-herpetic neuralgia, which are difficult conditions to treat. Thus, in the context of increasing pressure on healthcare budgets, vaccination can contribute to the sustainability of healthcare systems through reduced and more efficient use of healthcare resources.